Cultivating Green Minds: Enhancing Climate Literacy and Awareness in Azerbaijani Secondary Schools - Ismayilova, Saida (Dunakavics, 2024)
Climate change poses significant challenges globally, and Azerbaijan is no exception. However, there is a notable gap in climate literacy and awareness among the younger population in Azerbaijani secondary schools. This article addresses the pressing need to enhance climate education by integrating comprehensive environmental courses into the national curriculum. Despite some efforts, the current educational framework lacks the depth and breadth required to foster a robust understanding of climate issues among students. This gap not only hinders students’ ability to grasp the urgency of climate action but also limits their potential to contribute to sustainable practices and policies. To bridge this gap, we propose a multi-faceted approach that includes curriculum reform, teacher training, interactive learning methods, and community engagement. By incorporating climate science across various subjects and establishing dedicated environmental studies courses, we can provide students with a solid foundation in climate literacy. Furthermore, empowering teachers through professional development programs and creating opportunities for hands-on learning and extracurricular activities can significantly enhance students’ engagement and understanding. This article also emphasizes the importance of a community-based approach, involving parents, local organizations, and environmental groups to support and reinforce school-based initiatives. To ensure the proposed strategies are effective and suitable for Azerbaijan, we will analyze successful climate education models from different countries and assess their applicability to the Azerbaijani context.